PENGARUH CITRA MEREK DAN PROMOSI SEBAGAI STRATEGI DALAM PENINGKATAN PENJUALAN (Studi Kasus pada Distributor Emas “Diandra Gold” Demak) - Kusumawati, Dyah (Universitas YPPI Rembang, 2022)
This study was conducted with the aim of examining the effect of brand image and promotion on increasing sales at Diandra Gold as a Mini Gold distributor in Demak Regency. Sampling by purposive sampling as many as 87 respondents from 11 sub-districts in Demak Regency, Central Java. The analysis technique uses multiple linear regression with a Likert scale as the measurement scale. Testing the significance of the effect of the independent variable (brand image and promotion) on the dependent variable (sales increase) using SPSS. SPSS test results show that partially and simultaneously brand image and promotion variables have a positive and significant effect on increasing sales. The higher the brand image in the minds of consumers, the more product sales will increase. The more frequent promotions are carried out and also through other advertising variations, product sales will also increase. Besides that, other research still needs to be done with different variables. Keywords: brand image, promotion, sales